"Breaking the Silence" to Improve Cancer Survivorship Care for First Nations Peoples: A Study Protocol for an Indigenous Knowledge Translation Strategy. Issue 1 (3rd May 2018) - Gifford, Wendy; Thomas, Roanne; Barton, Gwen; Grandpierre, Viviane; Graham, Ian D.
There is a significant knowledge-to-action gap in cancer survivorship care for First Nations (FN) communities. To date, many approaches to survivorship have not been culturally responsive or community-based. This study is using an Indigenous knowledge translation (KT) approach to mobilize community-based knowledge about cancer survivorship into health-care programs. Our team includes health-care providers and cancer survivors from an FN community in Canada and an urban hospital that delivers Cancer Care Ontario's Aboriginal Cancer Program. Together, we will study the knowledge-to-action process to inform future KT research with Indigenous peoples for improving health-care delivery and outcomes. The study will be conducted in settings where research relations and partnerships have been established through our parent study, The National Picture Project. The inclusion of community liaisons and the continued engagement of participants from our parent study will foster inclusiveness and far-reaching messaging. Knowledge about unique cancer survivorship needs co-created with FN people in the parent study will be mobilized to improve cancer follow-up care and to enhance quality of life. Findings will be used to plan a large-scale implementation study across Canada.